[PP.06.11] ANTIANGIOGENETICS AND HYPERTENSION: EPIDEMIOLOGY AND BASAL FEATURES OF PATIENTS. (September 2016) - Destro, M.; Dognini, G.P.; Cagnoni, F.; Coinu, A.; Maccagni, G.; Barni, S.
Abstract : Objective: Antiangiogenetics (AAG) are used to treat a number of neoplasms by inhibiting Vascular Endothelial Growth Factor activity, blocking angiogenesis and inducing cancer cells death. A class effect common to all AAG is the raise of blood pressure (BP). Aim of this study was to evaluate cancer patients (pts) receiving an AAG to define basal features and aspects of AAG-related HTN (AAG-HTN). Design and method: Between March 2012 and January 2016, all cancer pts receiving an AAG at Treviglio-Caravaggio Hospital (Italy) were evaluated by a multidisciplinary team. They underwent Home, Office, and Ambulatory BP measurements, which were regularly repeated until 1 month after AAG withdrawal. HTN was defined and managed according to the ESH/ESC guidelines. Results: 55 consecutive AAG treated pts were evaluated (M/F = 38/17, median age:61, range:48–84yrs). Cancer sites were: colorectal (N = 21), kidney (N = 15), hepatocellular (N = 10), ovary (N = 2), lung (N = 1), double sites (N = 6). The employed AAG (including 5 pts who received 2 consecutive different AAG) were: bevacizumab (N = 24), sunitinib (N = 14), sorafenib (N = 13), pazopanib (N = 2), aflibercept (N = 2), regorafenib (N = 2), axitinib (N = 3). Before AAG starting 34 (61.8%) pts reported a history of HTN (in 8 a therapy adjustment was required because of uncontrolled HTN), moreover in 5 it was newly diagnosed. When cardiovascular risk factors were compared to general population, diabetes and smoking history resulted higher while dyslipidaemia was lower and cardio-cerebro-vascular events were similar. AAG-HTN was observed in 53%, including all the 5 AAG second lines, and was equally distributed among the various AAG compounds. Median time to AAG-HTN was 21 days (range 1day-2yrs): it was shorter for axitinib and regorafenib (1–5 days) and longer for sunitinib and bevacizumab (16days-2years). Conclusions: Basal evaluation before AAG treatment is crucial to improve pts management, since cancer pts display some peculiar features, including a slightly different cardiovascular risk factors profile and a high rate of HTN (with a significant rate of newly diagnosed HTN before AAG). While the higher incidence of AAG-HTN compared to previous studies may be due to a change in diagnostic criteria (NIH/CTCAE), main features of AAG-HTN are common to all the AAG, with the only difference in time to AAG-HTN arise.